Structural Characterization of 6-Halo-6-Deoxycelluloses by Direct-Dissolution Solution-State NMR Spectroscopy - Dryś, Magdalena; Koso, Tetyana V.; Kilpeläinen, Petri O.; Rinne‐Garmston, Katja T.; Todorov, Aleksandar R.; Wiedmer, Susanne K.; Iashin, Vladimir; King, Alistair W. T. (Wiley-VCH, 2024)
Regioselective modifications of cellulose using activated cellulose derivatives such as 6-halo-6-deoxycelluloses provide a convenient approach for developing sustainable products with properties tailored to specific applications. However, maintaining precise regiochemical control of substituent distribution in 6-halo-6-deoxycelluloses is challenging due to their insolubility in most common solvents and the resulting difficulties in precise structure elucidation by modern instrumental analytical techniques. Herein, an accessible NMR-based approach toward detailed characterization of 6-halo-6-deoxycelluloses, including the determination of the degrees of substitution at carbon 6 (DS6), is presented. It is shown that the direct-dissolution cellulose solvent, tetrabutylphosphonium acetate:DMSO-d6, converts 6-halo-6-deoxycelluloses to 6-monoacetylcellulose, enabling in situ solution-state NMR measurements. A range of 1D and 2D NMR experiments is used to demonstrate the quantitivity of the conversion and provide optimum dissolution conditions. In comparison with other NMR-based derivatization protocols for elucidating the structure of 6-halo-6-deoxycelluloses, the presented approach offers major advantages in terms of accuracy, speed, and simplicity of analysis, and minimal requirements for reagents or NMR instrumentation.
Keywords: 6-halo-6-deoxycelluloses; cellulose; degree of substitution; nuclear magnetic resonance; regioselective modification of cellulose